Forwarding strategies to online multiple-choice tests - Pramote Danpradit; Tanit Kongkumnerd; Pranrapee Boonplian (Gemilang Maju Publikasi Ilmiah (GMPI), 2021)
After the final test of the semester 2/2020 test results of the Aesthetic Appreciation courses (focus music content), learners did not score satisfactorily. The aesthetic Appreciation courses committee analyzed the problem together with the assessment results. This article is a study that compiles knowledge and ideas from academic documents and teaching experience in Aesthetic Appreciation courses, resulting in an article improving teaching using strategies do online multiple-choice tests as follows: 1) Ability to use a computer and typing skills. 2) Ability to read comprehension. 3) Ability to create multiple-choice, 4) Teaching as a tutor role, and 5) The online test, and points to be aware in online testing. In addition, the researcher will continue to apply this concept and create an online test in teaching. There are also ideas for teaching design. This research can be used for guideline in other courses in the future.